Pectus excavatum em filhote de cão - Relato de caso - Galvão, André Luiz Baptista [UNESP]; Toni, Maria Carolina [UNESP]; Mostachio, Giuliano Queiroz [UNESP]; Rossi, Adriana [UNESP]; Do Nascimento Braz, Larissa Ayane [UNESP]; Dias, Deborah Penteado Martins [UNESP]; Canola, Júlio Carlos [UNESP]; Carvalho, Marileda Bonafim [UNESP]; Tinucci-Costa, Mirela [UNESP] (My University, 2013)
The Pectus excavatum is a deformity of the costocartilages and sternum that result in a dorsoventral narrowing of the chest. This is deformity has been reported in dogs and cats. Although the etiology of Pectus excavatum is unknown, several theories have been postulated as possible causes, such as the shortening of the central tendon of the diaphragm, abnormalities of intrauterine pressure, a congenital deficiency of cranial muscles of the diaphragm and deformity of the upper airways. Animals with Pectus excavatum may be asymptomatic or may present with clinical signs associated with both respiratory and cardiovascular functions abnormalities.
Pectos excavatum in puppy - Case report
Keywords: Cyanosis; Dyspnea; Tachypnea